1916
DOI: 10.33915/agnic.160
|View full text |Cite
|
Sign up to set email alerts
|

The Residual Effects of Fertilizers

Abstract: Bookkeeper tin cooperation with the University of Chicago. *In cooperation .with the United States Department of Agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1917
1917
1998
1998

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…'Paper read as a part of the symposium on "Soil Organic Matter" at the meeting of the Society held in Washington, D. C., November Bear (2) in his studies of Dekalb soil at the West Virginia Experiment Station in 1916 concluded that quick lime caused a loss of organic carbon and nitrogen.…”
Section: J W Whitementioning
confidence: 99%
See 1 more Smart Citation
“…'Paper read as a part of the symposium on "Soil Organic Matter" at the meeting of the Society held in Washington, D. C., November Bear (2) in his studies of Dekalb soil at the West Virginia Experiment Station in 1916 concluded that quick lime caused a loss of organic carbon and nitrogen.…”
Section: J W Whitementioning
confidence: 99%
“…Bear ( 2) concluded from his studies of Dekalb soil at the West Virginia Experiment Station that the organic matter of a depleted soil can be increased and maintained in a rotation system through the systematic use of mineral fertilizers without the return of crop residues other than the roots and stubbles. Also, that the nitrogen content of the soil in like manner can be increased and maintained with9ut the use of mineral nitrogen or farm manure.…”
Section: Comparative Residual Effects Of Manure and Mineral Fertilizersmentioning
confidence: 99%
“…They state that Drew's organ- This is a denitrifying organism which produces ammonia by the reduction of nitrates. Bear and Salter (2) show that the lime requirement (Veitch) of the West Virginia Agricultural Experiment Station fertility plots is less where the content of organic matter has been increased, and suggest that this decrease may have been due to the precipitation of calcium from solution by the humus in the soil, whereby it was prevented from being lost in the drainage water.…”
Section: Hall and Millermentioning
confidence: 99%
“…Theory of differences in the kinds and quantities of nutrients required by plants. 3• Theory of differences in composition and habits of growth of plants in relation to the control of diseases and insects. 4.…”
mentioning
confidence: 99%
“…Paper read as a part of the symposium on "Crop Rotation" at the meeting of the Society held in Washington, D. C., November 19, 1926. Contribution from the Department of Soils, the Ohio State University, Columbus, Ohio.•Professor of Soils 3. Reference by number is to "Literature Cited," p. 533•…”
mentioning
confidence: 99%